Difficulty level of topics in senior school Arabic Language curriculum in Oke-Ogun, Oyo State, Nigeria - Lawal, Musibau Adebayo (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study examined teachers’ perception of the difficulty levels of topics in senior school Arabic curriculum. A total of 30 Arabic Language teachers from 30 senior schools constituted the study sample. The variables considered were teacher’s qualifications and years of teaching experience. A checklist containing all topics (82) of senior school Arabic Language curriculum was used for data collection. The study was anchored to four research questions. The content and face validity of the instrument were done by giving the checklist to two teachers of Arabic Language in senior secondary schools and specialists in Arabic education at the University of Ilorin. Test-retest was used to determine the reliability of the instrument. The data were analysed using frequency counts and percentages. The score of the first and the second times of administration of the checklist were correlated using Pearson r. The correlation coefficient value was 0.96. The findings revealed that seven topics were perceived to be very difficult; 18 topics were perceived to be difficult; while 57 topics were perceived to be not difficult by the respondent. Conclusion were drawn on the basis of these findings.